(untitled) (Jurnal Bina Praja, 2021)
In 2020 post-conflict regional head elections were held in Indonesia, including in North Sulawesi. Regulations concerning election explicitly state that each candidate is required to campaign and use environmentally friendly props. This study aims to analyze the perception of election organizers in North Sulawesi in implementing the 2020 election whether they have implemented an environmentally friendly concept. The research method is descriptive qualitative, with the determination of the sample is done by purposive sampling. In this case, the informant is the election organizer, the General Elections Commission (KPU), and the General Election Supervisory Agency of the Province and City Regencies in North Sulawesi. The results showed that the perception of the informants’ environment was at the highest level, namely ecocentric, meaning that the concept of being environmentally friendly was an important part of election success. But this perception was not applied in the socialization material they carried out during the 2020 post-conflict regional head election in North Sulawesi. Another finding in the observation in the city of Manado, the provincial capital of all candidates, tends to carry out a campaign model that is not environmentally friendly. It concluded that applying the concept of environmentally friendly elections is still below the level of expectations. Further intervention is needed so that in the future, the elections that are carried out will also ensure that an environmentally friendly concept is implemented.